Descriptive Memoir of Election Commission, April 1956 Government of India - Planning Commission (Planning Commission, 1956)
The office of the Election Commission was established 1 under Article 321 of the Constitution of India on the 25th January, 1950. Its main functions are (i) to superintend, direct and control the preparation of the electoral rolls for, and conduct of, all elections to Parliament and to the Legislature of every State and of elections to the offices of President, and Vice-President, and (ii) to appoint Election Tribunals to inquire into election petitions arising out of, or in connection with, elections to Parliament and to the Legislatures of States.
Government of India Cabinet Secretariat (O and M Division)